2015
DOI: 10.1177/1759091415578714
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Endothelin-1- and Bradykinin-Activated Store-Operated Calcium Entry in Afferent Sensory Neurons

Abstract: Endothelin-1 (ET-1) and bradykinin (BK) are endogenous peptides that signal through Gαq/11-protein coupled receptors (GPCRs) to produce nociceptor sensitization and pain. Both peptides activate phospholipase C to stimulate Ca2+ accumulation, diacylglycerol production, and protein kinase C activation and are rapidly desensitized via a G-protein receptor kinase 2-dependent mechanism. However, ET-1 produces a greater response and longer lasting nocifensive behavior than BK in multiple models, indicating a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Likewise, previous studies indicate that BK increased [Ca 2+ ] i in rat submucosal plexus (Avemary and Diener, 2010), myenteric neurons (Wurner et al, 2014), sensory neurons of trigeminal ganglia (Szteyn et al, 2015), or liver cells (Garcia-Sainz and Avendano-Vazquez, 1999). In cardiac vagal neurons, the effect of BK was mediated by B2 receptors, similarly to the response in rat submucosal plexus (Avemary and Diener, 2010) or liver cells (Garcia-Sainz and Avendano-Vazquez, 1999), while in myenteric neurons both B1 and B2 receptors were involved in the response (Wurner et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Likewise, previous studies indicate that BK increased [Ca 2+ ] i in rat submucosal plexus (Avemary and Diener, 2010), myenteric neurons (Wurner et al, 2014), sensory neurons of trigeminal ganglia (Szteyn et al, 2015), or liver cells (Garcia-Sainz and Avendano-Vazquez, 1999). In cardiac vagal neurons, the effect of BK was mediated by B2 receptors, similarly to the response in rat submucosal plexus (Avemary and Diener, 2010) or liver cells (Garcia-Sainz and Avendano-Vazquez, 1999), while in myenteric neurons both B1 and B2 receptors were involved in the response (Wurner et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…In cardiac vagal neurons of nucleus ambiguus, similarly to sensory neurons (Szteyn et al, 2015) or subcutaneous fibroblasts (Pinheiro et al, 2013), both Ca 2+ influx and Ca 2+ release from internal stores contributed to the increase in [Ca 2+ ] i produced by BK. Using a pharmacological approach, we identified that in nucleus ambiguus neurons BK triggers Ca 2+ entry via P/Q-type voltage-gated Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A late shoulder in the calcium response was apparent in cells exposed to 100 nM BK, as a result of entry of extracellular calcium through receptor-modulated calcium-permeable channels 21 or of the release of calcium through store-operated channels, 22 or of entry through voltage-gated Ca +2 channels in response to a depolarization caused by BK. 23 When extracellular [Ca +2 ] was at its physiological level, this shoulder was relatively unaffected by LID (10 mM), compared with the peak response (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, an earlier study demonstrated that bradykinin induces an increase in inositol 1,4,5-triphosphate (IP3) in neonatal rat cardiomyocytes 42 and bradykinin-mediated short nocifensive responses is related to activating PLC, followed by Orai1 in afferent sensory neurons. 18 In rat C6 glioma cells, bradykinin triggers Ca 2+ influx, resulting in calcium store Ca 2+ release, which is associated with nitric oxide generation for regulating permeability of blood-tumour barrier, 43 while in primary cultured rat brain microvascular endothelial cells, bradykinin-triggered Ca 2+ influx-induced Ca 2+ release is involved in regulation of the junction protein claudin-5. 19 A recent study shows that Ca 2+ signalling induced by bradykinin results from initial Ca 2+ release from ER IP3Rs followed by Ca 2+ entry through Ca 2+ release-activated channels in normal pancreatic stellate cells.…”
Section: Ca 2+ Signalling By Bradykinin and Intracellular Signal Momentioning
confidence: 99%